Molecular characterization of turtle-like protein in whiteleg shrimp (Litopenaeus vannamei) and its role in Enterocytozoon hepatopenaei infection - Velázquez-Lizárraga A.E. (2023)
Enterocytozoon hepatopenaei (EHP) is a microsporidian parasite that infects shrimp hepatopancreas, causing growth retardation and disease susceptibility. Knowledge of the host-pathogen molecular mechanisms is essential to understanding the microsporidian pathogenesis. Turtle-like protein (TLP) is part of the immunoglobulin superfamily of proteins, which is widely distributed in the animal kingdom. TLP has multiple functions, such as cell surface receptors and cell adhesion molecules. The spore wall proteins (SWPs) of microsporidia are involved in the infection mechanisms. Some SWPs are responsible for spore adherence, which is part of the activation and host cell invasion processes. Previous studies showed that TLP from silkworms (Bombyx mori) interacted with SWP26, contributing to the infectivity of Nosema bombycis to its host. In this study, we identified and characterized for the first time, the Litopenaeus vannamei TLP gene (LvTLP), which encodes an 827-aa protein (92.4 kDa) composed of five immunoglobulin domains, two fibronectin type III domains, and a transmembrane region. The LvTLP transcript was expressed in all tested tissues and upregulated in the hepatopancreas at 1 and 7 days post-cohabitation (dpc) and at 9 dpc in hemocytes. To identify the LvTLP binding counterpart, recombinant (r)LvTLP and recombinant (r)EhSWP1 were produced in Escherichia coli. Coimmunoprecipitation and enzyme-linked immunosorbent assays demonstrated that rLvTLP interacted with rEhSWP with high affinity (KD = 1.20 × 10−7 M). In EHP-infected hepatopancreases, LvTLP was clustered and co-localized with some of the developing EHP plasmodia. Furthermore, LvTLP gene silencing reduced the EHP copy numbers compared with those of the control group, suggesting the critical role of LvTLP in EHP infection. These results provide insight into the molecular mechanisms of the host–pathogen interactions during EHP infection.